Associations Between Genetic Variants in Vitamin D Metabolism and Asthma Characteristics in Young African Americans: A Pilot Study. (1st August 2011) - Pillai, Dinesh K.; Iqbal, Sabah F.; Benton, Angela S.; Lerner, Jennifer; Wiles, Andrew; Foerster, Matthew; Ozedirne, Tugba; Holbrook, Henry P.; Payne, Perry W.; Gordish-Dressman, Heather; Teach, Stephen J.; Freishtat, Robert J.
Abstract : Introduction: Low vitamin D levels have been associated with asthma severity in children. Young, urban African Americans (AAs) have high rates of hypovitaminosis D and asthma. Our objective was to determine associations between variants in vitamin D metabolism genes and asthma characteristics in a pilot study of young urban AAs. Materials and Methods: Two urban AA cohorts of subjects aged 6 to 20 years (139 subjects with asthma and 74 subjects without asthma) were genotyped for 12 single nucleotide polymorphisms (SNPs) in 3 vitamin D metabolism genes: VDR (vitamin D receptor), CYP24A1 (cytochrome P450 vitamin D 24-hydroxylase), and CYP2R1 (cytochrome P450 vitamin D 25-hydroxylase). In a case-control analysis, SNPs were studied for associations with an asthma diagnosis. Within the asthmatic cohort, SNPs were analyzed for associations with quantitative asthma characteristics. All analyses were adjusted for age, sex, and body mass index percentile. Results: Only the CYP2R1 SNP rs10766197 homozygous minor genotype was associated with asthma ( P = 0.044). CYP24A1 SNP rs2248137 was associated with lower vitamin D levels ( P = 0.006). Within the asthma cohort, multiple significant associations between SNPs and asthma characteristics were identified; VDR SNP rs2228570 was associated with the higher nighttime asthma morbidity scores ( P = 0.04), lower baseline spirometric measures ( P < 0.05), 1 or more positive aeroallergen skin test ( P = 0.003), and increased immunoglobulin E levels ( P < 0.001). Discussion: This pilot study demonstrates that variants in vitamin D metabolism genes are associated with quantitative asthma characteristics in young, urban AAs. The collection of these associations provides evidence for the need for a large population-based study of vitamin D-relevant SNPs in this cohort.